Malnutrition is associated with increased disease risk in older people in the Makkah region of Saudi Arabia: A cross-sectional study - Althaiban, Maha A.; Aljefree, Najlaa M.; Almoraie, Noha M.; Shatwan, Israa M. (Frontiers in Public Health, 2023)
Introduction: There is little research on the nutritional status of older people in Saudi Arabia. This study investigated the factors associated with the nutritional status of older people in the Makkah region, Saudi Arabia. We hypothesized that older people who are at risk of malnutrition are at higher risk of different diseases. Materials and Methods: This cross-sectional study surveyed 271 people aged ≥60 years from October 2021 to January 2022. The data collected included demographic and anthropometric measurements, the Geriatric Depression Scale-Short Form, Geriatric Oral Health Assessment Index, Mini Nutritional Assessment, and Eating Attitudes Test. Results: Among the 271 participants, 13.3% were malnourished, 53.9% were at risk of malnutrition, 72.3% had poor oral health, 43.2% felt depressed, and 20.3% had eating disorders. Poor oral health, depression, and eating disorders were more prevalent, and the household diversity score higher, among participants at risk of malnutrition compared with those with a normal nutritional status (P<0.001), supporting our original hypothesis. Conclusion: Malnutrition and nutritional status were associated with overweight or obesity, poor oral health, depression, and eating disorders. Older people had a high risk of malnutrition.